Costs and benefits of extended parental care in Tundra Swans Cygnus columbianus columbianus - Earnst, Susan L; Bart, Jonathan (Wildfowl, 2013)
Short-term costs and benefits of extended parental care were studied in Tundra Swans feeding onÂ tubers of aquatic vegetation on an autumn migratory stopover and feeding on clams on the winteringÂ grounds. In both seasons, families were dominant over non-parents and may have maintainedÂ access to better feeding sites as a result. Parents fed less intensively than non-parents during bothÂ seasons. Parents and cygnets did not differ from non-parents in frequency of, or time spent in,Â agonistic interactions in either season. Cygnets appeared to exploit the foraging behaviour of theirÂ parents in two ways: 1 ) cygnets copied parents’ feeding sites in both seasons; and 2) during the autumn, cygnets dabbled for vegetation churned to the surface by parents. When feeding on clams during the winter and being kleptoparasitized by gulls, cygnets sought protection from gulls by approaching parents, and parents threatened gulls more than did non-parents.